Assessment of the Chemical Composition and Antioxidant Capacity of Flowers, Seeds, and Seed Cake of Cactus Pear (Opuntia ficus-indica L.) and Their Application in Biscuits - Fatiha Brahmi; Amira Oufighou; Leila Smail-Benazzouz; Nouna Hammiche; Lydia Hassaine; Lila Boulekbache-Makhlouf; Khodir Madani; Federica Blando (Resources)
Functional ingredients rich in bioactive compounds can be added to conventional ingredients for the formulation of food to increase its nutraceutical potential. Three prickly pear parts, namely flowers, seeds, and seed cake were utilized in the current work as natural antioxidant resources. The flower extract gave the best amounts of antioxidants as estimated by spectrophotometric methods, which were 68.08 mg GAE/100 g DM for total phenolics; 6.91 mg QE/100 g DM for total flavonoids; 13.05 mg QE/100 g of DM for flavonols; and 0.22 mg/100 g of DM for condensed tannins. The three extracts showed a high proportion of antioxidant effect as determined by DPPH, ABTS, FRAP, and TAA in vitro assays. Chemical analysis and sensory testing were performed on biscuits that were made by adding powdered flowers, seeds, or seed cake. The biscuits made from the seed cake gave a higher protein content (83.97 mg/100 g) and the biscuits made from the seeds had the best ash concentration (3.21%), while the biscuits containing flower powder had the highest anti-radical activity (81.04%). Sensory analysis disclosed the preference for biscuits formulated with flowers or seeds (80%) by the experts. These findings demonstrated that the nutritional value of the biscuits was improved by their enrichment with cactus parts powders, and they were appreciated by tasters.